A double-blind, placebo-controlled, single-ascending-dose intravenous infusion study of rHIgM22 in subjects with multiple sclerosis immediately following a relapse. Issue 2 (April 2022) - Greenberg, Benjamin M.; Bowen, James D.; Alvarez, Enrique; Rodriguez, Moses; Caggiano, Anthony O.; Warrington, Arthur E.; Zhao, Ping; Eisen, Andrew
Background: Recombinant human immunoglobulin M22 (rHIgM22) has promoted remyelination in animal models and was well tolerated in people with clinically stable multiple sclerosis. Objective: Safety/tolerability of a single rHIgM22 dose was investigated following an acute relapse and to determine whether this enhanced CNS/CSF concentrations. Methods: Adults (N = 27) with acute relapse were assigned to rHIgM22 (0.5 or 2.0 mg/kg) or placebo. Study included screening/steroid administration periods and 10 study visits over 6 months. rHIgM22 CSF concentrations were assessed on days 2 and 29. Pharmacokinetic and safety samples were taken for up to 60 days. Assessments included adverse events and other clinical measures. Brain magnetic resonance imaging was performed with/without gadolinium. Results: rHIgM22 CSF levels were consistent with dose-dependent concentration on both days 2 and 29. Infusion was generally well tolerated during an acute relapse. Immunogenicity was mild. Most adverse events did not appear to be dose dependent, were mild/moderate, and were events often associated with multiple sclerosis. Conclusion: Although limited by high variability and small sample size, the data suggest enhanced CNS uptake associated with a drop in CSF levels. This study demonstrated safety of an antibody directed to myelin and oligodendrocytes in the course of active demyelinating disease. Further research into rHIgM22 is warranted. ClinicalTrials.gov : NCT02398461https://clinicaltrials.gov/ct2/show/NCT02398461